Unexpected falsely high vancomycin concentrations in a patient with endocarditis during routine therapeutic drug monitoring - Laura Galán-Caballero; María del Rosario Salas-Butrón; Daniel Lozano-Martín; Iván Alejandro Díaz-Rengifo; Isabel Ortega-Madueño; Lucia Diaz-Garcia; Ana Isabel Terleira-Fernández (European Journal of Case Reports in Internal Medicine)
Introduction: Vancomycin is a glycopeptide antibiotic indicated for the treatment of infections caused by methicillin-resistant Staphylococcus aureus. Appropriate vancomycin therapeutic drug monitoring is an essential exercise to improve the achievement of the target therapeutic levels. Case description: An 87-year-old female was admitted with diagnosis of endocarditis. She was started on antibiotic therapy with intravenous vancomycin. The first vancomycin level registered in our hospital was 36.4 µg/ml. Because this value exceeded the critical threshold (15–20 µg/ml) the prescription was interrupted. New vancomycin concentration tests were indicated for the next days with 65.8 µg/ml, 73 µg/ml, 55.1 µg/ml, 77.9 µg/ml and 100 µg/ml results. Two samples were reanalysed in Hospital Universitario La Paz and were undetectable. Our Clinical Analysis Department found an analytical interference; however, the responsible molecule could not be identified, so the clinical team changed antibiotic treatment to daptomycin, and the infectious condition of the patient improved. Conclusions: It is recommended that clinicians have a high index of suspicion to investigate cases where drug concentrations do not correlate with clinical expectations. Healthcare professionals need to understand that occasional interference still occurs due to the binding of proteins.